Le tact au cœur de la parole professorale - Eirick Prairat (Recherches en Éducation)
In this article, we propose a reflection on the professorial speech. Before being expositive or questioning, before being didactic, the professorial speech is seeking a link. The professorial speech is originally ethical. The first part of this text explores the two great facets of language: language as an instrument of thought and language as an instance that connects us. In the second part, we show that the virtue which is at the heart of the professorial speech is the virtue of tact because tact is just as much sense of address as sense of appropriateness. Finally, in the third and last part, we show that the quality of the link, in terms of teaching, is not measured by a degree of proximity but by the way in which the teacher makes the right.